2014
DOI: 10.1097/meg.0000000000000201
|View full text |Cite
|
Sign up to set email alerts
|

Unemployment, public-sector healthcare spending and stomach cancer mortality in the European Union, 1981–2009

Abstract: Increases in unemployment are associated with a significant increase in stomach cancer mortality. Stomach cancer mortality is also affected by public-sector healthcare spending. Initiatives that bolster employment and maintain public-sector healthcare expenditure may help to minimize increases in stomach cancer mortality during economic downturns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Unemployed people are often vulnerable to the poor health effects of economic recession because of government budget austerity in health and social welfare spending during these periods 33 . Other studies have reported that mortality due to stomach cancer 34 and cerebrovascular diseases 35 among unemployed people increased, possibly because of reductions in health care expenditure. In contrast, mortality rates for cancers and ischaemic heart disease in unemployed people have steadily reduced, even during Japan’s economic crisis.…”
Section: Discussionmentioning
confidence: 98%
“…Unemployed people are often vulnerable to the poor health effects of economic recession because of government budget austerity in health and social welfare spending during these periods 33 . Other studies have reported that mortality due to stomach cancer 34 and cerebrovascular diseases 35 among unemployed people increased, possibly because of reductions in health care expenditure. In contrast, mortality rates for cancers and ischaemic heart disease in unemployed people have steadily reduced, even during Japan’s economic crisis.…”
Section: Discussionmentioning
confidence: 98%
“…As EMR treatment can be used only in the early stage of gastric cancer, we inferred that low-income status leads to lower probability for early diagnosis of cancer. This delayed detection consequently leads to a higher mortality rate [16][17][18][19][20][21]. Carstairs index is an indicator for neighborhood deprivation; a positive, higher score on the index denotes greater deprivation EMR endoscopic mucosal/submucosal resection Relationship between socioeconomic status and accessibility for endoscopic resection among… 65…”
Section: Discussionmentioning
confidence: 99%
“…The expenditure measure was total national health expenditure in eight studies, [46][47][48][49][50][51][52][53] public sector or government spending on health in three studies, [54][55][56] per incident case cancer spending in two studies, 3,57 and per capita cancer drug spending in one study. 58 Four studies included both developed and developing countries across five continents, [48][49][50][51] while the rest focused primarily on developed countries in North America and Europe.…”
Section: International Comparisons Of Spending and Outcomesmentioning
confidence: 99%
“…51 Four studies on international comparisons used a time series design with country-level fixed effects, and all found higher spending to be associated with lower mortality. [54][55][56][57] The most salient evidence on the cross-country comparisons comes from an individual-level, longitudinal analysis of cancer registries from 11 countries. 3 The authors found that from 1995 to 1999, each $20,000 increase in spending per patient with cancer was associated with an additional 2.3 years of life expectancy after diagnosis for the average patient with cancer.…”
Section: International Comparisons Of Spending and Outcomesmentioning
confidence: 99%